RESIDENT AS TEACHER IN CLERKSHIP: STUDENTS’ AND RESIDENTS’ PERCEPTION - Nurrahma Wahyu Fitriyani; Ova Emilia; Doni Widyandana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2018)
Background: Resident has a significant role and time allocation as a clinical teacher in the learning process of medical students at the clerkship stage in clinical settings. Unfortunately, residents were often not formally asked to be involved in the teaching process. Residents’ role in medical students’ learning process in clerkship is still ill defined. The aim of this study was to explore the perceptions of resident and medical students on residents’ role as a teacher in clerkship using cognitive apprenticeship model.Methods: This study used quantitative descriptive, cross sectional design. Samples taken with total sampling were 153 students (68.3%) and 214 resident (60.6%) of the total population. Respondents were asked to fill The Maastricht Clinical Teaching Questionnaire (MCTQ), and the results were analyzed using ANOVA and independent t-test.Results: Results of quantitative analysis showed a difference of perception between students and residents in modeling (p = 0.008) and overall performance (p = 0.002) factor, in which students placed a higher point than the resident. These results were consistently found in three departments. While in three other, students gave a lower point than the resident. In addition, differences also found in the exploration factor based on residents’ study period and residents’ preferences for teaching.Conclusion: Residents’ role as a clinical teacher in clerkship is very important, especially as a role model for students. Taking into account of time allocations spent between students and the residents, improvement and optimalization of residents’ role as a clinical teacher appears to be an important requirement.